Genotype-phenotype correlation in children with autosomal dominant polycystic kidney disease - Fencl, Filip; Janda, Jan; Bláhová, Kveta; Hríbal, Zdenek; Stekrová, Jitka; Puchmajerová, Alena; Seeman, Tomás (Pediatric nephrology (Berlin, Germany), 2009)
Adults with autosomal dominant polycystic kidney disease (ADPKD) and PKD1 mutations have a more severe disease than do patients with PKD2 mutations. The aim of this study was to compare phenotypes between children with mutations in the PKD1/PKD2 genes. Fifty PKD1 children and ten PKD2 children were investigated. Their mean age was similar (8.6 +/- 5.4 years and 8.9 +/- 5.6 years). Renal ultrasound was performed, and office blood pressure (BP), ambulatory BP, creatinine clearance and proteinuria were measured. The PKD1 children had, in comparison with those with PKD2, significantly greater total of renal cysts (13.3 +/- 12.5 vs 3.0 +/- 2.1, P = 0.004), larger kidneys [right/left kidney length 0.89 +/- 1.22 standard deviation score (SDS) vs 0.17 +/- 1.03 SDS, P = 0.045, and 1.19 +/- 1.42 SDS vs 0.12 +/- 1.09 SDS, P = 0.014, successively] and higher ambulatory day-time and night-time systolic BP (day-time/night-time BP index 0.93 +/- 0.10 vs 0.86 +/- 0.05, P = 0.021 and 0.94 +/- 0.07 vs 0.89 +/- 0.04, P = 0.037, successively). There were no significant differences in office BP, creatinine clearance or proteinuria. Prenatal renal cysts (14%), hypertension defined by ambulatory BP (27%) and enlarged kidneys (32%) were observed only in the PKD1 children. This is the first study on genotype-phenotype correlation in children with ADPKD. PKD1 children have more and larger renal cysts, larger kidneys and higher ambulatory BP than do PKD2 children. Renal cysts and enlarged kidneys detected prenatally are highly specific for children with PKD1.
Keywords: Humans; Polycystic Kidney, Autosomal Dominant; dítě; polycystické ledviny autozomálně dominantní; Hypertension; Child; ledviny; Female; kationtové kanály TRPP; Kidney; Phenotype; Ultrasonography; Genotype; lidé; Blood Pressure Monitoring, Ambulatory; ambulantní monitorování krevního tlaku; ultrasonografie; ženské pohlaví; krevní tlak; Male; Retrospective Studies; hypertenze; fenotyp; genotyp; retrospektivní studie; TRPP Cation Channels; mužské pohlaví; Blood Pressure